Productivity of Introduced Trigona Bees in The Green Open Space of Universitas Sumatera Utara - Doni Aldo Samuel Siahaan; Suci Rahayu; Irin Surani; Adrian Hartanto (International Journal of Science and Environment (IJSE), 2026)
Trigona spp. is one of the social insects that can be cultivated in open spaces, urban areas, or through a practice known as meliponiculture. Introduced colonies rely on surrounding vegetation for nectar, pollen, and resin, which are essential for supporting the queen, colony, and larvae to maintain overall colony health. Green open spaces are often underutilized, serving primarily as areas for human activities. This study aims to evaluate the success of introducing Trigona spp. bees and assess the potential of the green open space at the Universitas Sumatera Utara campus as a small-scale honey production industry. The results indicated that foraging activities continued despite the rainy season (October, November) during the two-month observation period. A total of 18 ornamental and shade plants were identified as nectar and pollen sources, with two key species namely Mangosteen (Garcinia mangostana: Clusiaceae) and Mango (Mangifera indica: Anacardiaceae), serving multifunctional roles in colony establishment. Productivity, as measured by the number of nest structures such as brood cells, pollen pots, and honey pots, reached 284, 46, and 85 units, respectively, with an average honey volume of 42.6 mL. Stepwise regression analysis yielded an equation indicating that total honey production was related to the combined activity of outgoing bees and incoming bees carrying pollen. These findings support the integration of Trigona spp. colonies into campus green spaces as a viable honey production industry, aligning with the university’s vision to create lush environments for academic and research activities.